Effects of heat stress on oxidative balance and sperm quality in dogs - Burgio, Matteo; Forte, Lucrezia; Prete, Andrea; Maggiolino, Aristide; De Palo, Pasquale; Aiudi, Giulio Guido; Rizzo, Annalisa; Carbonari, Alice; Lacalandra, Giovanni Michele; Cicirelli, Vincenzo (Frontiers in Veterinary Science, 2024)
IntroductionHeat stress negatively affects both animal reproductive performance and their overall wellbeing and welfare. When temperatures soar, the body responds to maintain balance, resulting in heat stress. This triggers various responses, including the buildup of reactive oxygen species (ROS), which can harm sperm vitality through lipid peroxidation. Oxidative damage can result in sperm dysfunction. This study aimed to evaluate the effects of environmental heat stress on canine quantitative and qualitative ejaculate parameters.MethodsThirty-six male crossbred dogs were involved in the trial. This study was performed in 2022, precisely from May to August. Dogs were subdivided in two groups, one heat stressed (HS) and one in thermoneutrality (TN). Thermo Hygrometric Index (THI) was hourly measured and ranged from 60 to 71 in TN dogs and from 60 to 83 for HS dogs. Semen and blood samples were collected at 30-day intervals, starting from May (0 days), and then at 30 days, 60 days, and 90 days and analysis for evaluating biochemical profile, semen oxidative status, and semen quality were performed.ResultsIn HS dogs, serum total protein, albumin, and urea concentrations showed a significant decrease after 60 days (P < 0.01), with values lower than those observed in TN dogs (P < 0.01). Both catalase and glutathione peroxidase concentrations were reduced after 60 days in HS dogs, showing lower levels than the TN group (P < 0.01 and P < 0.05, respectively). Antioxidant potential increased over time in HS dogs, reaching higher values at 60 days (P < 0.05) and 90 days (P < 0.01). On the other hand, ROS in the sperm of HS animals rose by day 90, surpassing the values recorded at previous time points and in TN dogs (P < 0.01). Semen concentration (P > 0.01) and total sperm count (P < 0.05) declined after 30 days in the HS group and remained lower than the TN group throughout the trial.DiscussionThe study demonstrates that heat stress negatively affects the oxidative status and sperm quality of male dogs, reducing reproductive performance. However, further research is needed due to the lack of complete breed homogeneity in the study groups.